P Pengaruh Modal Psikologis terhadap Kinerja melalui Burnout di PT PLN (Persero) UID Jawa Timur - Chinta Ayuning Putri; Anang Kistyanto (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
The purpose of this study is to analyze the effect of psychological capital on employee performance through burnout on employees of PT PLN (Persero) East Java Distribution Unit. The sampling technique used a saturated sample with 40 respondents in the employees of PT PLN (Persero) East Java Distribution Unit. The results of this study explain that psychological capital has no effect on burnout. Psychological capital has a positive and significant effect on employee performance. Burnout does not affect employee performance. And found the results that it is not proven that burnout has an intervening role between psychological capital on employee performance.